Alternative penalties in Qatari and Jordanian legislation - Al-Zuobi, Mikhlid Ibrahim (Revue jurisprudence; Vol. 11 No 02 (2019): مجلة الاجتهاد القضائي, 2019)
This study aims at identifying the alternative penalties in the Qatari and Jordanian legislations, then the concept of alternative sanctions and social service were identified. The qualitative approach was applied in this study. The current study has reached a number of conclusions, the most important of which was that alternative sanctions do not mean the suspension of the original sanctions, but instead, convicted person is subjected to alternative sanctions instead of the deprivation of liberty.   The Qatari legislator provided for the sanction of social service as one of the sanctions stipulated in the Qatari and the Jordanian Penal Code. A person convicted to a social service sentence shall be liable to carry out social service six hours per day, in accordance with the method and in the manner determined by the decision of the Attorney General.